Optimalisasi Pelayanan Digital Perpustakaan Universitas Wijaya Kusuma di Era Pandemi Covid 19 - Yanuastrid Shintawati (Pustabiblia: Journal of Library and Information Science, 2021)
Libraries as one of the information service providers do not escape the obligation to break the chain of COVID 19, they work around this by closing, reducing the number of visitor and changing their information services from manual to electronic or digital information services, even though in previous activities electronic services have also been held but is increasing due to the impact of COVID 19. University libraries in general and the UWKS Library in particular already have organized digital services with electronic repositories, e-book collections, e-journal subscriptions in line with the needs of the academic community who need information quickly and often they get it without having to come to the library because of the ease of access from anywhere with the help of information technology. This study aims to describe the optimization of digital services at the Wijaya Kusuma University Library in its role in meeting the information needs of the academic community, using a qualitative descriptive research approach with librarian staff, user and the Head of the Wijaya Kusuma University Library as resource persons. The results show that the UWKS Library already has and serves digital information from various digital media, namely: E-library, E-reporitory, E-journal owned and managed by various study programs within the Wijaya Kusuma University Surabaya and subscribes to Emerald insight in in the fields of engineering and economics, but its utilization is still not maximized because there has been no socialization and training to utilize digital information sources properly and correctly